A phase I study to assess the mass balance, excretion, and pharmacokinetics of [(14)C]-ixazomib, an oral proteasome inhibitor, in patients with advanced solid tumors - Gupta, Neeraj (Invest New Drugs, 2017)
This two-part, phase I study evaluated the mass balance, excretion, pharmacokinetics (PK), and safety of ixazomib in patients with advanced solid tumors. In Part A of the study, patients received a single 4.1 mg oral solution dose of [(14)C]-ixazomib containing ~500 nCi total radioactivity (TRA), followed by non-radiolabeled ixazomib (4 mg capsule) on days 14 and 21 of the 35-day PK cycle. Patients were confined to the clinic for the first 168 h post dose and returned for 24 h overnight clinic visits on days 14, 21, 28, and 35. Blood, urine, and fecal samples were collected during Part A to assess the mass balance (by accelerator mass spectrometry), excretion, and PK of ixazomib. During Part B of the study, patients received non-radiolabeled ixazomib (4 mg capsules) on days 1, 8, and 15 of 28-day cycles. After oral administration, ixazomib was rapidly absorbed with a median plasma T(max) of 0.5 h and represented 70% of total drug-related material in plasma. The mean total recovery of administered TRA was 83.9%; 62.1% in urine and 21.8% in feces. Only 3.23% of the administered dose was recovered in urine as unchanged drug up to 168 h post dose, suggesting that most of the TRA in urine was attributable to metabolites. All patients experienced a treatment-emergent adverse event, which most commonly involved the gastrointestinal system. These findings suggest that ixazomib is extensively metabolized, with urine representing the predominant route of excretion of drug-related material. Trial ID: ClinicalTrials.gov # NCT01953783.